(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article explores the language and practical processes of translating irony between two different language systems: Uzbek and English. It focuses on Abdulla Qodiriy’s famous historical novel O‘tkan Kunlar (Days Gone By) to show how verbal and structural irony are recreated for Western readers. The study uses Relevance Theory and Skopos Theory to evaluate how translators move away from wordfor-word translation to rebuild hidden meanings based on context. The article highlights the role of translation strategies like modulation and explicitation in preserving the original artistic voice